Consumer attitudes and preferences regarding Italian quality wines. evidence from the civintas exhibition - Marangon F.; Troiano S. (Food quality products in the advent of the 21st century: production, demand and public policy, 2005)
In order to improve consumer behaviour knowledge, it is very important to collect information about consumer characteristics and preferences. This is made possible at events such as Civintas, an Italian quality food exhibition that promotes production linked to a specific territory, such as CDO (Controlled Designation of Origin) wines. The 1997-2000 editions gave us the opportunity to gather information through interviews with participants. This analysis allowed us to understand the demand market configuration. We should underline that the study was also used to give the consumer product information, so as to improve their perception of quality. Interviewees were asked to respond to questions regarding socio-economic characteristics and wine preferences. The responses were used to create consumer profiles. Data was analysed in three statistical stages: univariate, bivariate and multivariate analysis. A homogeneity analysis was conducted to examine data during the last stage. A hedonic analysis model was also carried out to identify the implicit prices in relation to wine quality. After conducting this study, it was discovered that wine consumption was characterised by a wide variety of consumer behaviours and preferences. This information will be useful in indicating effective market segmentation criteria so as to develop sustainable differentiation and positioning strategies to satisfy consumer preferences.
83. EAAE Seminar on Food Quality Products in the Advent of the 21st Century: Production, Demand and Public Policy, 2003/09/04-07, Chania (Greece)